Religion, Nationalism and Ethics in Political Campaigns - Wibisono, Adwin (JURNAL KOMUNIKASI INDONESIA, 2018)
Artikel ini mengkaji penggunaan unsur-unsur agama dalam kampanye politik di Indonesia dari perspektif etis. Penulis berpendapat bahwa penggunaan isi agama dalam kampanye politik adalah kerugian dari sudut pandang etis - khususnya teleologis - karena menyimpang dari tujuan akhirnya untuk mencapai kebaikan yang lebih besar. Untuk mendukung argumen ini, tulisan ini meneliti penggunaan isi agama untuk tujuan politik dari sudut pandang etika teleologis yang mengacu pada karya-karya dalam etika, etika politik, dan komunikasi serta pemikiran tentang nasionalisme. This article examines the use of religious elements in political campaigns in Indonesia from an ethical perspective The author argues that the use of religious contents in political campaigns is detriment from an ethical – specifically teleological – point of view as it deviates from its ultimate purpose of achieving the greater good. To support this argument, the paper examines the use of religious contents for political purposes from a teleological ethics point of view referring to the works in ethics, political ethics, and its communications as well as thoughts on nationalism